Assessing well-being using hierarchical needs - Matthew Clarke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Determining whether well-being has improved is an important multidisciplinary task. It is important therefore to develop a multidimensional measure of well-being that reflects a wide spectrum of human needs. A new approach is presented in this paper based on multidimensional hierarchical human needs and motivation. Improving well-being within this multidimensional approach requires progressive satiation of hierarchical needs. Eight indicators have been chosen to reflect these four hierarchical categories. This paper empirically applies this new measure of well-being to eight Southeast Asian countries for the period 1985-2000: Cambodia, Indonesia, Lao PDR, Malaysia, Philippines, Singapore, Thailand and Vietnam. Results for Australia are also provided as a comparative benchmark.
Keywords: I31; O15; O57; 330; well-being; Maslow; Southeast Asia; Lebensqualität; Grundbedürfnisse; Motivation; Südostasien